Transient Catalytic Activity of a Triazole‐based Gelator Regulated by Molecular Gel Assembly/Disassembly. Issue 3 (24th January 2017) - Araújo, Marco; Escuder, Beatriu
Abstract: An amphiphilic molecular gelator functionalized with a triazole fragment that exhibits a transient self‐assembly behavior in the presence of copper is presented. This dynamic dissipative system composed by a triazole‐based molecular gel coordinating copper(I) is able to catalyze the model 'click' reaction, achieving 71 % conversion in the first three hours. This high catalytic activity is derived from the assembly/disassembly cycles of the gelator, promoted by the model "click" reaction between benzylazide and phenylacetylene. The consumption of these reactants was found to regulate the dynamic behavior of the gelator, influencing the properties and catalytic performance of the copper(I) coordination gel. The creation of a hydrophobic environment promotes the disassembly and migration of the metallogel to solution, resulting in an increased catalytic efficiency. The newly synthesized metallogel catalyst could be re‐used for three consecutive runs without any loss of its catalytic performance and without the need of being isolated between each catalytic cycle. Abstract : Transient catalysis. A dynamic catalytic system is described in which an amphiphilic gelator functionalized with an azidocoumarine triazole fragment shows a transient self‐assembly/disassembly behaviour regulated by the presence of the reactants. The system shows temporary catalytic activity towards a model 'click' reaction that vanishes upon consumption of the reagents and reappearance of a gel phase.